A Case Study Color as a Visual Language: Focused on TV Commercial - Cindy Muljosumarto (Institute of Research and Community Outreach - Petra Christian University, 2017)
Color is an important element of a visual design, it also an essential element in a TV Commercial (TVC). This paper examined color as a ‘language’ to convey the TVC message to the audience, using Kobayashi’s Color Image Scale to be the color descriptor combined with psychological colors theory and some data from professionals. To gain more specific result the data also compared with an experimental method that has been done with a group of potential target audience of this product. The last step is an analysis and conclusion. The result will be a new finding about color function in advertising and hopefully could lead into new creative ideas of TVC ads.